A Case Series of Young Patients with Completely Reversed Severe Pulmonary Hypertension - Balegadde, Aniketh Vijay (J Clin Diagn Res, 2017)
Pulmonary Arterial Hypertension (PAH) is a progressive symptomatic disorder, which may ultimately lead to death if left untreated. Although majority of PAH cases are idiopathic, pulmonary hypertension resulting due to certain underlying conditions are also observed frequently. In such cases, it becomes essential to identify any potentially treatable or reversible causes for PAH. There have been significant advances in the medical management of PAH and various medicines have been approved by US Food and Drug Administration (FDA) for various stages of PAH. With these therapies, there can be varying degrees of improvement in the pulmonary artery pressures and hemodynamic profile. Therefore, physiologic reversal can and does occur, sometimes to the point of normalization. We hereby present three such cases of severe PAH in patients below 50 years of age due to various aetiologies like left heart disease, isolated unilateral absence of right pulmonary artery with hypoplastic right lung and factor V Leiden mutation associated pulmonary thromboembolism, all of whose pulmonary artery pressures are completely normalised with adequate treatment of the underlying disease and with optimised medications for PAH, ultimately leading to tapering and stoppage of PAH medications.